Experience drives the development of movement-cognition correlations in a butterfly - Snell-Rood, Emilie C.; Steck, Meredith (Frontiers in Ecology and Evolution, 2015)
Correlations between behavioral traits are widespread, but the developmental genetic architecture of such correlations is poorly characterized. Understanding the developmental mechanisms that lead to correlations between behaviors has implications for predicting how changing environments might alter the strength, direction and persistence of these associations. Here we test the idea that genetic variation in one behavioral trait can drive the development of traits related to a second behavior, resulting in correlations between them.. We focus on correlations between movement and aspects of cognition, in particular accuracy of decision making and neural investment. Such syndromes have been seen across a variety of systems, from insects to birds, but the direction of the correlation often varies. We use cabbage white butterflies as a system because they are easy to rear in large numbers and show ample genetic variation in both movement and learning, facilitating a split-sibling design. We test the prediction that variation in established proxies for movement at emergence will be correlated with the development of cognitive traits later in life (in siblings). Our results suggest that genotypes (full-sibling groups) that emerge with more elongate wings explore their environment more rapidly. In addition, genotypes that emerge with relatively smaller thoraxes are more likely to learn to search for atypical host plants and subsequently develop larger brains and brain regions. Taken together, genotypes that invest less in flight are slower, better learners and develop larger brains. These data are consistent with the idea that movement can drive the development of other behavioral traits, resulting in the emergence of correlated behaviors.